Fixed-Luminance and Multi-Luminance Flicker Electroretinography Parameters in Patients with Early Active Birdshot Chorioretinopathy. (2nd January 2022) - Maleki, Arash; Ueberroth, Jordan A.; Manhapra, Ambika; Walsh, Marisa; Asgari, Soheila; Chang, Peter Y.; Anesi, Stephen D.; Foster, C. Stephen
ABSTRACT: Purpose: To evaluate the parameters of the Fixed-Luminance and Multi-Luminance flicker electroretinography protocol among patients with early active birdshot chorioretinopathy. Methods: Fixed-Luminance magnitude, Fixed-Luminance phase, Multi-Luminance magnitude area under the curve, and Multi-Luminance phase area under the curve parameters were compared between early active birdshot chorioretinopathy patients and an age-matched control group. Results: There was no statistically significant difference between the Fixed-Luminance flicker magnitude ( P = .6), the Fixed-Luminance flicker phase ( P = .9), and the Multi-Luminance flicker phase area under the curve ( P = .55) when each was compared to the normal population; however, the difference between the mean Multi-Luminance flicker magnitude area under the curve in our patients and the healthy control group was statistically significant. ( P = .003) Conclusions: Multi-Luminance flicker magnitude area under the curve has been shown to be significantly different from the normal population in the early active course of the disease. Abbreviations: BSCR: birdshot chorioretinopathy; cd: Cadmium; ERG: Electroretinography; FA: Fluorescein angiography; FL-: Fixed-luminance; HVF: Humphrey visual field; Hz: Hertz; ICG: Indocyanine green; m 2 : Square meter; ML-: Multi-luminance; ms: millisecond; SITA: Swedish interactive thresholding algorithm; SWAP: Short wave-length automated perimetry